1977
DOI: 10.1182/blood.v49.6.903.903
|View full text |Cite
|
Sign up to set email alerts
|

Marrow culture studies in adult acute leukemia at presentation and during remission

Abstract: Culture of bone marrow and/or blood cells in a semisolid agar system from 43 adults with acute nonlymphoblastic leukemia at first presentation showed two distinct growth patterns at 14 days. In 53% of patients cells failed to grow (type O), while in the remainder an abnormal growth pattern (type B) with small numbers of diffuse colonies and excessive numbers of cell clusters was seen. The response following chemotherapy was significantly better in the patients whose cells failed to grow. Serial culture studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Later, Spitzer et al (1976 ) modified these patterns and also showed that cases without in vitro proliferation achieved complete remission more frequently than those that had shown in vitro growth. Although these findings have been confirmed in some studies ( Browman et al , 1983 ; Vincent et al , 1977 ), they were not reproduced in others ( Mertelsmann et al , 1981 ). Moreover, when methyl‐cellulose was used in cultures, no relationship was observed between the in vitro growth and response rate ( Aul et al , 1992 ; Marie et al , 1983 ).…”
mentioning
confidence: 83%
“…Later, Spitzer et al (1976 ) modified these patterns and also showed that cases without in vitro proliferation achieved complete remission more frequently than those that had shown in vitro growth. Although these findings have been confirmed in some studies ( Browman et al , 1983 ; Vincent et al , 1977 ), they were not reproduced in others ( Mertelsmann et al , 1981 ). Moreover, when methyl‐cellulose was used in cultures, no relationship was observed between the in vitro growth and response rate ( Aul et al , 1992 ; Marie et al , 1983 ).…”
mentioning
confidence: 83%